Journal of enterprising communities people and places in the global economy. (Emerald Group Publishing, 2007)
Focuses on enterprise, people and places, a topic critical in the global economy as it is evolving. Increasingly the events critical to the sustainable prosperity of people (culturally, socially, economically and environmentally) are being played out at the nexus of the local or the community (people in places) and the transnational (corporations, groups and movements of the civil sector, and supranational organizations and agreements).